(untitled) (Revista de Estudos da Linguagem, 2024)
This paper aims to investigate the social meaning of the realizations [z] and [ʒ] of the fricative archiphoneme before coronal sounds /n, l/ in the speech of Rio Grande do Norte (RN). Based on the theoretical and methodological assumptions of Sociolinguistics (Weinreich; Labov; Herzog, 2006 [1968]; Labov, 2008 [1972]), we organized a sample of perception data collected through a questionnaire of linguistic attitudes, prepared according to the matched-guise technique (Lambert et al., 1960) and hosted on the Google Forms platform. The analyzed sample contains responses from 76 individuals to 8 attribute scales, distributed in the categories of competence, personal integrity, social attractiveness and geographic association, in addition to a scale of speech similarity and assignment tasks of educational level, age group, professional activity and hometown. The analysis is performed by ordinal and multinomial logistic regression methods, using the ordinal (Christensen, 2019) and mclogit (Elff, 2022) packages, executed in the R software (R Core Team, 2022). The results indicate that evaluations of the phonetic forms of /S/ vary according to the subsequent segment. When followed by /n/, a context in which the palatal form seems to be predominant in the speech of the community, the realizations [z, ʒ] are, in general, equally evaluated. On the other hand, in front of /l/, a context in which palatalization is apparently not very productive, a preference for the alveolar realization is indicated as a mark of regional identity, although there is no record of stigmatization of the variant [ʒ].